2021
DOI: 10.1002/ctm2.326
|View full text |Cite
|
Sign up to set email alerts
|

A microbiota‐based predictive model for type 2 diabetes remission induced by dietary intervention: From the CORDIOPREV study

Abstract: Dear Editor,Type 2 diabetes is widely considered as a chronic, progressive disease that is a consequence of the seemingly inexorable decline in β-cell function. 1 However, recent studies have demonstrated that in the early stages of development, it may be reversible. Indeed, in this regard, primary support derived from patients undergoing bariatric surgery has provided the earliest evidence of type 2 diabetes remission. In fact, the normalization of plasma glucose levels can occur in some patients just days af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Recent studies suggest that lower alphadiversity and the characteristic of a pro-inflammatory environment in gut microbiota dysbiosis promote insulitis by activating and proliferating pancreatic-draining lymph node T cells, particularly diabetogenic CD8+ T cells, which may contribute to the risk of developing type 1 diabetes (T1D) in genetically predisposed individuals (9). In the case of type 2 diabetes (T2D), gut microbial taxa can serve as a biomarker for disease diagnosis (10) and predicting remission (11), which interact with dietary constituents to modulate inflammation, affect gut permeability, glucose and lipid metabolism, insulin sensitivity, and overall energy homeostasis, involving in the pathophysiology of T2D (12). DKD is one of the most common and serious complications of diabetes, and the emerging role of its gut microbiota has attracted wide attention and is considered an important factor affecting the occurrence and development of DKD.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that lower alphadiversity and the characteristic of a pro-inflammatory environment in gut microbiota dysbiosis promote insulitis by activating and proliferating pancreatic-draining lymph node T cells, particularly diabetogenic CD8+ T cells, which may contribute to the risk of developing type 1 diabetes (T1D) in genetically predisposed individuals (9). In the case of type 2 diabetes (T2D), gut microbial taxa can serve as a biomarker for disease diagnosis (10) and predicting remission (11), which interact with dietary constituents to modulate inflammation, affect gut permeability, glucose and lipid metabolism, insulin sensitivity, and overall energy homeostasis, involving in the pathophysiology of T2D (12). DKD is one of the most common and serious complications of diabetes, and the emerging role of its gut microbiota has attracted wide attention and is considered an important factor affecting the occurrence and development of DKD.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, flavonoids and quinones were also observed in the 235 differential metabolites (Figure 5C). The categories of amino acids (14), fatty acids (13), lineolic acids (10), terpene lactones (6), glycerophosphoethanolamines (6), bile acids and derivatives (6), and eicosanoids (6) were also among the top differential metabolites (Figure 5C). Furthermore, the above-mentioned 18 key differential gut microbial species correlated with the top 50 abundant differential metabolites.…”
Section: Effect Of Dietary Licorice On Gut Metabolitesmentioning
confidence: 99%
“…Dietary interventions are the most practical approach for large‐scale health interventions [ 5 ]. In recent years, dietary interventions have been used for the prevention or treatment of Alzheimer's disease [ 6 ], endometriosis [ 6 ], weight gain in childhood, acute lymphoblastic leukemia [ 7 ], cardiovascular disease [ 8 ], depression [ 9 ], and type 2 diabetes [ 10 ]. For example, tea extracts have been preventing Alzheimer's disease by inhibiting acetylcholinesterase activity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in recent years have also confirmed that the imbalance of gut microbiota involves many links from diabetes to diabetic nephropathy, such as insulin secretion disorder, advanced glycation end products, chronic inflammatory state, etc. ( 3 ), and the identification of intestinal microflora may be used as a biomarker for diagnosing and predicting diseases ( 4 , 5 ). However, the number of cells, bacteria and genes contained in the gut microbiota is very large, so its functional contribution to DN has not been systematically characterized.…”
Section: Introductionmentioning
confidence: 99%
“…(3), and the identification of intestinal microflora may be used as a biomarker for diagnosing and predicting diseases (4,5). However, the number of cells, bacteria and genes contained in the gut microbiota is very large, so its functional contribution to DN has not been systematically characterized.…”
Section: Introductionmentioning
confidence: 99%